Exploring Materiality and Connectivity in Anthropology and Beyond (University College London, 2020)
Exploring Materiality and Connectivity in Anthropology and Beyond provides a new look at the old anthropological concern with materiality and connectivity. It understands materiality not as defined property of some-thing, nor does it take connectivity as merely a relation between discrete entities. Somewhat akin to Heisenberg's uncertainty principle, it sees materiality and connectivity as two interrelated modes in which an entity is, or more precisely - is becoming, in the world. The question, thus, is how these two modes of becoming relate and fold into each other. Throughout the four-year research process that led to this book, the authors approached this question not just from a theoretical perspective; taking the suggestion of 'thinking through things' literally and methodologically seriously, the first two workshops were dedicated to practical, hands-on exercises working with things. From these workshops a series of installations emerged, straddling the boundaries of art and academia. These installations served as artistic-academic interventions during the final symposium and are featured alongside the other academic contributions to this volume. Throughout this process, two main themes emerged and structure Part II, Movement and Growth, and Part III, Dissolution and Traces, of the present volume, respectively. Part I, Conceptual Grounds, consists of two chapters offering conceptual takes on things and ties - one from anthropology and one from archaeology. As interrelated modes of becoming, materiality and connectivity make it necessary to coalesce things and ties into thing~ties - an insight toward which the chapters and interventions came from different sides, and one in which the initial proposition of the editors still shines through. Throughout the pages of this volume, we invite the reader to travel beyond imaginaries of a universe of separate planets united by connections, and to venture with us instead into the thicket of thing~ties in which we live.